2019
DOI: 10.1515/jbcpp-2018-0178
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure-reducing activity of Gongronema latifolium Benth. (Apocynaeceae) and the identification of its main phytochemicals by UHPLC Q-Orbitrap mass spectrometry

Abstract: BackgroundGongronema latifolium Benth. (family Apocynaceae) leaves (GL) has interesting medicinal properties. The effects of extracts from G. latifolium on blood pressure (BP) and the possible mechanisms of action were also investigated.MethodsThe ultrahigh resolution liquid chromatography orbitrap MS analysis was used to identify the phytochemicals present. Normotensive Wistar rats were anesthetized with sodium pentobarbitone (40 mg/kg) intraperitoneally, and the jugular vein was cannulated for infusion of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…This would have shown the blood pressure pattern and electrical activity in this model of myocardial injury. However, a previous study from our laboratory has shown that GL leaves extract has blood pressure lowering effect under normotensive conditions (Beshel et al, 2019). Also, the expression of apoptotic markers in the heart and liver was not measured.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This would have shown the blood pressure pattern and electrical activity in this model of myocardial injury. However, a previous study from our laboratory has shown that GL leaves extract has blood pressure lowering effect under normotensive conditions (Beshel et al, 2019). Also, the expression of apoptotic markers in the heart and liver was not measured.…”
Section: Discussionmentioning
confidence: 94%
“…This is in line with previous reports that the GL extract has anti‐lipid peroxidation and antioxidant properties which are attributed to the presence of phytochemicals such as alkaloid, saponin, tannins, and flavonoids (Okoko & Silas‐Olu, 2021). We previously demonstrated that the extract of GL leaf is rich in saponins, triterpenes, coumarins, and flavonoids, of which kaempferol and rutin were the most abundant (Beshel et al, 2019) that have antioxidant potentials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the C-reactive protein levels in the two treated group is an indication of the anti-inflammatory potential of G. latifolium which may be due to the flavonoid and polyphenols in the plant extract [29]. A study reported that flavonoids present in G. latifolium leaves extract are kaempherol, kaempferol 3-O-rutinoside, rutin and laricitrin-3-Oglucoside [30]. Kaempferol and the rutinoside, and rutin have anti-inflammatory and antioxidant activity [31,32].…”
Section: Discussionmentioning
confidence: 98%
“…phytochemicals maintains homodynamic function of heart rate and significantly prevents heart failure (Paulino et al, 2019;Beshel et al, 2019). During the MI development the cardiac membrane becomes damaged which has resulted in the outflow of cardiac tissue enzymes to the blood stream.…”
Section: Discussionmentioning
confidence: 99%